Teacher-Student Interaction in English Language Learning: A Case Study of A Fourth-Grade Student with Speech Delay at Binari Green School - Rahmawati, Rahmawati; Rafiqa, Syarifa; Juhana, Juhana (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to describe the forms of interaction between teachers and 4th-grade students with speech delay in English language learning, analyze the influence of such interactions on students' speaking abilities, and identify the instructional challenges faced by teachers in inclusive classrooms. A qualitative case study approach was employed at Binari Green Primary School in Tarakan, North Kalimantan. The subject was a 10-year-7-month-old male student diagnosed with speech delay by a psychologist. Data were collected through classroom observations, semi-structured interviews, documentation, and pre- and post-assessments. The findings revealed that teacher-student interactions were consistent and supported by multimodal strategies such as visual aids, modeling, guided questioning, and collaborative activities. These structured interactions positively influenced the student's oral English proficiency by reducing affective barriers, enhancing confidence, and providing necessary scaffolding. However, challenges were encountered, including limited verbal responses, public speaking anxiety, and the need for individualized teaching approaches. The study concludes that fostering inclusive, adaptive, and student-centered interactions is crucial for promoting English language development in students with speech delay.